Clearing the circles: an unusual way - Vickneswaran, Kanesan; Nambi, Rabi (International Journal of Research in Medical Sciences, 2025)
A 66-year-old lady with no significant past medical history presented with gradual onset of annular erythematous raised border with central clearing and atrophy plaque on her left arm. Subsequently, she noticed further plaques on her left forehead, and extensor surfaces of her arms. A diagnostic skin punch biopsy was organised from the affected site on right arm. The histology showed multi-nucleated giant cells with surrounding fragmented elastic fibres and elastophagocytosis with no dermal mucinosis and no interface inflammation. A working diagnosis of annular elastolytic giant cell granuloma (AEGCG) was formulated. Initially this was treated with a potent topical steroid, followed with tacrolimus ointment but the dermatoses did not settle. She was then started on hydroxychloroquine 200 mg twice daily. A repeat follow-up in three months showed the plaques has started to flatten out and the treatment was continued for a further three months. The patient was happy with the improvement of the rash. AEGCG is an uncommon granulomatous skin reaction typically involving sun exposed areas of the body. Clinically, this presents as annular erythematous plaques with central clearing or atrophy. The gold standard for diagnosis is based on histopathology showing granulomatous inflammation, multinucleated giant cells with more than one area of elastophagocytosis and absence of necrobiosis. There is no standard treatment, but treatment can range from topical therapy with corticosteroids, to phototherapy including narrow band ultraviolet B to systemic medications including oral antimalarial such as hydroxychloroquine. This case illustrates that hydroxychloroquine can be used as a treatment option.